Multi-injection turbine housing: a novel concept for tip-leakage improvement in radial turbines - Liu, Hao (2017)
Secondary flow injection is a way which allows for the efficiency of a turbomachine to be increased further, after blade design optimizations have already been performed. In this paper, a novel method in improving turbine performance using secondary flow injection through an injection slot over the turbine shroud is investigated. A steady state numerical analysis of a low pressure mixed flow turbine was conducted. A baseline model without the injection slot was first validated against existing experimental data and reasonable agreement was found between the experiment and simulation results. Then, the shroud of the turbine was modified to include an injection slot from which a secondary injection flow enters and exits the turbine. The simulations were performed at a rotational speed of 30,000 rev/min, and the main performance parameters monitored are: total-to-static pressure ratio, non-dimensional mass flow parameter, isentropic velocity ratio, total-to-static isentropic efficiency, and blade torque. The effects of injection mass flow and direction were studied, and the parameters varied were the injection mass flow and yaw angle. The results show that generally, injection increases the power output of the turbine, although the power input of the injected fluid cancels out the power gain and results in no significant net gain in efficiency. The largest turbine power and efficiency gains were obtained at operating points with high isentropic velocity ratio. Also, the yaw angle of the injection had a significant effect on both turbine power and efficiency. However, when injection mass flow is reduced accordingly to maintain the same injection velocity at different yaw angles, the effect of injection yaw angle was smaller, suggesting that injection velocity might be a dominant factor in changing turbine performance. Flow visualization and blade loading diagrams show that injection has two main effects on the flow. Firstly, it energizes the leakage vortex which travels close to the suction surface, improving blade tip loading. Secondly, if injected with a significant circumferential velocity in the same direction of the blade rotation, the injected flow increases blade torque directly by entraining fluid near the blade tip to ‘push’ the blade, but this pushes the leakage vortex away from the suction surface as well. Overall, secondary injection at a yaw angle of 60° can provide an overall work increase of up to 11.4 percentage points over the baseline model, while injection at 45° yaw can provide up to 1.9 percentage points increase in efficiency at high velocity ratios. If the injection can be performed without any additional system power input, the net performance improvements can be very significant. Indeed this concept could represent a valid solution to recover exhaust gas which are discharged through the wastegate valve without contributing to any additional performance/power output improvement; the results obtained are explained and discussed in detail in the paper.